Hubungan Disiplin dan Motivasi terhadap Prestasi Kerja Pegawai di PT Pierlite Graha Nusantara - Hartono, Hendry (Binus Business Review, 2011)
Discipline represents primary factor which follows to determine the successful an organization in attainment of target. Motivation represents psychological processes which express interaction among attitude, perception requirement, and decision that happened at someone itself. Performance represents size measure of result (output) and benefit (outcomes) from an activity process at certain function, executed by someone as individual, and also by group of people at certain range of time. Good discipline which happened in a company can increase someone performance. And also do the things of with motivation had by an employee. Higher motivation level of employee will make the employee have high commitment to finish his/her jobs better. Employees those owning high commitment to finish its work mean this employee have achieving his/her own performance. Which in company happened good discipline and supported with high motivation from each; every employee, hence by itself officer employee performance also progressively mount. Thereby, hypothetically that by together there are can be anticipated that by together there are relation.Â